Gender and Dermatology (Springer International Publishing, 2018)
This book comprehensively reviews the characteristics of the body reflected in the skin due to differences in gender. It investigates the genetic and hormonal differences that can affect skin structure and function, and resulting in variations between women and men. The aging process and exogenous factors that differ according to differences in lifestyle between the sexes are also covered. Gender and Dermatology comprehensively outlines the various aspects of physiological differences between the skin of women and men using practical examples and review of the basic science. It is therefore an important clinically-relevant review for both the trainee and experienced practitioner in dermatology, primary care, geriatrics and immunology, while also being of interest to researchers in genetics and metabolic medicine. .